Effects of rope skipping exercise on working memory and cardiorespiratory fitness in children with attention deficit hyperactivity disorder - Huang, Ziyun; Li, Liang; Lu, Yijuan; Meng, Jie; Wu, Xueping (Frontiers in Psychiatry, 2024)
Introduction Children with Attention Deficit Hyperactivity Disorder (ADHD) exhibit deficits in working memory (WM) and cardiorespiratory fitness (CRF), both of which are closely associated with the core symptoms of ADHD. This study aimed to investigate the effects of rope skipping exercise (RSE) on the WM and CRF of children with ADHD, to provide a theoretical foundation for the optimization of exercise intervention programs tailored to children with ADHD. Methods This study recruited 55 children (age range 6–12 years) and randomly assigned them into three groups: the ADHD with RSE (AWRSE, n=22, mean age: 10.18 ± 1.10 years), the ADHD with sports game (SG) (AWSG, n=16, mean age: 9.38 ± 0.96 years), and the typically developing (TD) control group (CG, n=17, mean age: 8.94 ± 0.56 years). The AWRSE underwent a RSE intervention, while the other two groups participated in SG. The exercise intervention lasted for 8 weeks, with sessions held twice a week for 60 minutes each, at a moderate-to-vigorous-intensity (64–95% HRmax). All children in each group underwent pre-test and post-test, including height, weight, BMI, n-back, and 20mSRT. One-way analysis of variance (Ony-way ANOVA) and paired sample t-test were used to analyze inter- and intra-group differences respectively. Results Before the intervention, children with ADHD exhibited a significantly lower VO2max compared to the TD children (p<0.05), and there was no significant difference in the other indicators between the groups (p>0.05). After the intervention, no significant inter-group differences were found across all indices for the three groups of children (p > 0.05). The AWRSE had significant improvements in the accuracy of 1-back task, Pacer (laps), and VO2max (p<0.05), with the level of CRF approaching that of TD children. A significant decrease in response time for the 1-back task was observed in the CG. Conclusion An 8-week RSE intervention is an effective therapeutic approach for children with ADHD, significantly enhancing their WM and CRF.